2021
DOI: 10.1007/s40620-021-01165-0
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy in a patient with COVID-19 infection

Abstract: Case descriptionA 29-year-old South Asian male presented with fever, myalgia and lower limb swelling of 3 days duration. Four weeks prior to presentation, he had been diagnosed with COVID-19 infection and was treated symptomatically in the community isolation facility.He was diagnosed to have nephrotic syndrome with proteinuria of 8.71 g/24 h and serum albumin of 22 g/L. He also had acute kidney injury with peak serum creatinine of 145 µmol/L, estimated glomerular filtration rate (eGFR) of 65 mL/min per 1.73 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…In our study, NELL1-associated MN was found in the kidney, and the activated complement system in the liver exacerbated MN by MAC ( Cravedi, 2021 ). MN has rarely been reported in human COVID-19 infection ( Guo et al, 2022 ) or vaccination ( Aydin et al, 2021 ), with only a small fraction of these cases being PLA2R-positive. Hence, the observation of MN in our study provides new insights into SARS-CoV-2 infection-associated renal manifestations, although whether the MN in macaques is primary or secondary remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, NELL1-associated MN was found in the kidney, and the activated complement system in the liver exacerbated MN by MAC ( Cravedi, 2021 ). MN has rarely been reported in human COVID-19 infection ( Guo et al, 2022 ) or vaccination ( Aydin et al, 2021 ), with only a small fraction of these cases being PLA2R-positive. Hence, the observation of MN in our study provides new insights into SARS-CoV-2 infection-associated renal manifestations, although whether the MN in macaques is primary or secondary remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In total, five cases of MN associated with SARS-CoV-2 infection have been identified before 6 September 2022 in four articles [ 9 , 10 , 11 , 12 ] ( Table 1 )—all new, including one female and four males. Four elderly cases had a previous chronic medical history, especially hypertension.…”
Section: New-onset Mn Post Sars-cov-2 Infectionmentioning
confidence: 99%
“…All patients underwent kidney biopsy (phospholipase A2 receptor (PLA2R)—two positive, three negative; viral particles, all negative). Only one case [ 11 ] presented with PLA2R-Ab positive expression. The auxiliary examination of four cases suggested acute kidney injury (AKI) at admission.…”
Section: New-onset Mn Post Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kudose et al detected MN in five (6.6%) of 76 infected patients, and PLA2R was positive in two of them ( 17 ). In one reported case, a patient presented MN PLA2R positive 4 weeks after diagnosis of mild COVID-19, with nephrotic syndrome, AKI and partial response to immunosuppressive treatment ( 19 ).…”
Section: Morphological Kidney Findings Associated With Covid-19 Infec...mentioning
confidence: 99%